A Review of Preclinical Studies to Understand Fear During Adolescence. (February 2015) - Kim, Jee Hyun; Ganella, Despina E
<x xml:space="preserve">Abstract</x> The most rapid physical and psychological growth occurs during adolescence, a period of transition from childhood to adulthood when the incidence of anxiety disorder peaks in humans. Human and animal studies suggest that dramatic changes in prefrontal cortical areas during adolescence are responsible for such prevalence of anxiety. Only recently, however, has the relationship between prefrontal immaturity and differential fear processing across adolescence been directly and systematically examined. Such progress is largely due to the culmination of rodent studies that delineated the fear learning, expression, and inhibition neural circuitry, and preclinical studies that provided avenues for translation. This article summarises those initial findings on the circuitry of fear inhibition, and describes in detail the new findings on adolescent fear inhibition that highlight the prefrontal cortex as a key, unrefined brain region that may govern adolescent vulnerability to anxiety disorders. Specifically, adolescent rodents have been demonstrated to be impaired in inhibiting learned fear responses following fear extinction due to prefrontal immaturity, a discovery that was shortly after replicated in adolescent humans (at least the behavioural component). Our desire for this article is to acquaint both research and clinical psychologists with the neural circuitry of fear learning and extinction, turn the attention to developmental work, and facilitate translation of preclinical rodent findings in humans.